Screening And Identification Of Bacterial Isolate Producing Arbutin Glycoside And Improving Its Productivity By Mutagenesis - M.I., Noor; M.S, Nidhal (South Eastern European Journal of Public Health, 2024)
From three sources of Iraqi soil, 30 bacterial isolates were obtained. after performing the primary isolation process, 12 isolates could produce the glycoside arbutin as an indication of the reddish-brown precipitate. When secondary isolation was conducted, it was found that two isolates, A7 and C10, gave the highest production of arbutin as a function of the concentration of the resulting compound, as it reached a concentration of Arbutin 5.3 µg/ml and 8.5 µg/ml, respectively. The diagnosis process was carried out for isolate C10 based on cultural and microscopic characteristics, as the nature of growth on the liquid medium was that it floated on the surface, and the cells formed a thin membrane with each other. Pellice as for the nature of growth on a liquid media, the colonies were spread out and flat, with irregular edges, a cream color, and a wrinkled surface, while the microscopic characteristics of the bacterial isolate were that they were positive for Gram stain and the cells were rod-shaped of medium length. The biochemical tests Vitec 2 results showed that the bacterial isolate belonged to Bacillus subtilis with a probability of 98%. Upon genetic diagnosis at the 16SrRNA level, it was found that the isolate belonged to the genus Bacillus subtilis by 100% compared to what is available in the NCBI GenBank and that exposure for 30 minutes at a wavelength of 257 nanometers (20w) and at a distance of (20) cm from the dish to ultraviolet radiation resulted in to improve the production of arbutin twice as much as the wild strain.